Rozumienie emocji jako gwarancja racjonalnych zachowań uczestników rynków finansowych - Drabik, Ewa; Drabik, Iwona (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
Stock exchange analysts as well as financial markets researchers have come to the conviction that assets prices are based not only on current economic indicators and data referring to markets but also on emotions, preferences and psychological condition of market participants. Thus, it is to assume that abilities of perceiving and analysing other people’s emotions are a highly desirable quality characterizing potential bankers and stock brokers. This ability plays a particularly relevant role when the sequence of actions initiated on financial markets is quite unpredictable and when many world economies enter a simultaneous recession. In critical situations financial markets should leave no room for risk-seekers who engage themselves in sophisticated stock exchange games. Reasonability, common sense and ability of controlling extreme emotional states – these are highly preferable values. In order to estimate risk-loving players the appropriate selection of human resources in a financial sector is of fundamental importance. The aim of this paper is to examine whether potential bankers – in this case represented by students of the Faculty of Finance and Banking at Warsaw University of Life Sciences – are able to effectively perceive as well as assess their own and other people’s emotional states. In order to fi nd out whether the above specified target group meet the aforementioned criteria, their emotional intelligence has been studied.